2014
DOI: 10.1051/alr/2014006
|View full text |Cite
|
Sign up to set email alerts
|

Do cannibalistic fish forage optimally? An experimental study of prey size preference, bioenergetics of cannibalism and their ontogenetic variations in the African catfishHeterobranchus longifilis

Abstract: -This study relied on the day-by-day analysis of bioenergetics and prey size preference in isolated cannibals of the African catfish Heterobranchus longifilis (13-57 mm standard length, 3-500 mg dry body mass, n = 153) that were offered ad libitum conspecific prey of adequate sizes in small-sized (2-L) environments under controlled conditions (12L:12D, 30• C). In these conditions, cannibals of increasing body size selected preferentially prey of decreasing size relative to their own, and increasingly closer to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
9
3

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 10 publications
(15 citation statements)
references
References 71 publications
3
9
3
Order By: Relevance
“…Indeed, we showed that simply considering a non-constant biomass conversion efficiency can solve most problems encountered with previous models. In addition, empirical data suggest that there is indeed an optimal size of prey size where predation is the most efficient (Baras et al, 2014;Norin and Clark, 2017). Our model is, in a sense, closer to data and observations and one might argue that such adaptive dynamics models really tell us how food webs emerge from eco-evolutionary processes.…”
Section: Discussionsupporting
confidence: 68%
See 1 more Smart Citation
“…Indeed, we showed that simply considering a non-constant biomass conversion efficiency can solve most problems encountered with previous models. In addition, empirical data suggest that there is indeed an optimal size of prey size where predation is the most efficient (Baras et al, 2014;Norin and Clark, 2017). Our model is, in a sense, closer to data and observations and one might argue that such adaptive dynamics models really tell us how food webs emerge from eco-evolutionary processes.…”
Section: Discussionsupporting
confidence: 68%
“…Conversely, if preys are very small, a predator has to feed on a large number of preys and then the handling time (per unit of biomass) becomes critical. This suggests that λ 0 should depend on z − y as a function ξ(z −y), accordingly to empirical results (Baras et al, 2014;Norin and Clark, 2017), where ξ(z − y) should converge to zero when z − y converges to ±∞.…”
Section: Necessity Of a Trade-off On Conversion Efficiencysupporting
confidence: 56%
“…In contrast, the emergence of cannibalism was dependent strictly on the development of oral teeth at the embryonic stage (Baras et al 2000a, b), suggesting that fish hatching slightly later, or developing at a slightly slower rate than others, incur a major penalty for this very short delay. In particular, this is likely to apply to fish species with oral teeth that facilitate the exercise of incomplete cannibalism (which does not require that the cannibal be larger than its victim), as individuals with a slightly faster growth than others during the first days of exogenous feeding would not be safe from cannibalism (Baras et al 2014). The size advantage gained through the exercise of type I cannibalism at the embryonic and larval stages, later enables cannibals to exert type II cannibalism over smaller siblings, resulting in high mortality throughout the larval and early juvenile stages (Hecht and Appelbaum 1988;Baras 1999b).…”
Section: Size-sortingmentioning
confidence: 99%
“…Due to species-dependent morphological differences, the variability of dimensions during ontogeny and behaviour typical of a given species, diverse mathematical models are applied. The most commonly used models include those based on direct measurements of total length (TL) of cannibals and their prey or models based on such parameters as mouth width (MW), mouth gape (MG), body depth (BD) of a prey, head depth (HD) of a prey and head width (HW) of a prey (Folkvord and Otterå 1993;Baras and Dalmeida 2001;Hseu 2002;Kailasam et al 2002;Kestemont et al 2003;Hseu et al 2003b;Fessehaye et al 2005;Wallat et al 2005;Hseu et al 2007;Policar et al 2013;Baras et al 2014;Hseu and Huang 2014;Ribeiro and Qin 2015).…”
Section: Size-sortingmentioning
confidence: 99%
See 1 more Smart Citation